Carvacrol prevents acrylamide-induced oxidative and inflammatory liver damage and dysfunction in rats - Cerrah, Serkan; Ozcicek, Fatih; Gundogdu, Betul; Cicek, Betul; Coban, Taha Abdulkadir; Suleyman, Bahadir; Altuner, Durdu; Bulut, Seval; Suleyman, Halis (Frontiers in Pharmacology, 2023)
Background: Acrylamide causes hepatotoxicity with the effect of oxidative stress and inflammatory processes. Carvacrol is a monoterpenic phenol with antioxidant and anti-inflammatory properties. Aims: To determine the effects of carvacrol on oxidative liver injury induced by acrylamide administration in rats. Methods: Rats were divided into three groups of six animals each: healthy group acrylamide group (ACR), and acrylamide + carvacrol group (TACR). First, carvacrol (50 mg/kg) was administered intraperitoneally to the CACR group. One hour later, acrylamide (20 mg/kg) was given orally to the ACR and CACR groups. This procedure was performed for 30 days, after which the animals were sacrificed. The malondialdehyde (MDA) and total glutathione (tGSH) levels, total oxidant (TOS) and total antioxidant status (TAS), tumor necrosis factor-alpha (TNF-α), interleukin-1beta (IL-1β), and nuclear factor kappa b (NF-κB) were measured in the excised liver tissues. Alanine aminotransferase (ALT) and aspartate aminotransferase (AST) levels were determined in blood serum samples. Liver tissues were also examined histopathologically. Results: In the ACR group, malondialdehyde, TOS, ALT, AST levels, and NF-κB, IL-1β, and TNF-α levels were found to be high, and tGSH and total antioxidant status levels were low. In addition, diffuse degenerative changes and necrosis in hepatocytes, and moderate inflammation in the portal region were detected in the liver tissues of the ACR group. While carvacrol prevented the biochemical changes induced by acrylamide, it also alleviated the damage in the histological structure. Conclusion: Carvacrol may be used for liver damage caused by acrylamide.